2015
DOI: 10.15341/mese(2333-2581)/03.01.2015/008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction on Infrastructure Projects in the Zambian Construction Industry through Integrated Risk Management (IRM) Approach

Abstract: Construction projects are risk prone and as a consequence projects may have quality shortfalls, disputes, time and cost overruns. Realizing that huge sums are spent by the government in providing infrastructure, the research focused on assessing the feasibility of reducing risks on infrastructure projects through IRM. To achieve this, secondary data was obtained from an extensive literature review while primary data was through the use of a questionnaire survey to consultants and contractors. This revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…To secure their projects and consequently their businesses, contractors have no choice but to obtain securities and CAR insurance. These findings show a relationship with the study by Chipozya et al (2013) but not to the same extent. They indicated that sharing of risks in the Zambian construction industry is often done, and it was acknowledged as one of the best ways of mitigating risks.…”
Section: Knowledge About Securities and Contractors' All Risk Insurancesupporting
confidence: 53%
“…To secure their projects and consequently their businesses, contractors have no choice but to obtain securities and CAR insurance. These findings show a relationship with the study by Chipozya et al (2013) but not to the same extent. They indicated that sharing of risks in the Zambian construction industry is often done, and it was acknowledged as one of the best ways of mitigating risks.…”
Section: Knowledge About Securities and Contractors' All Risk Insurancesupporting
confidence: 53%